Corporate social responsibility in family firms: Can corporate communication affect CSR performance? - Battisti, Enrico; Nirino, Niccolò; Leonidou, Erasmia; Salvi, Antonio (My University, 2023)
Drawing on the stewardship theory (ST) and socio-emotional wealth (SEW) perspective, this study investigates the role of sustainable activities within family firms (FFs) and the effect of marketing strategic decisions in improving their corporate social responsibility performance. To achieve the research aims, we analysed a sample of 730 American and European listed companies from 2015 to 2020. The results show that family businesses are more socially responsible than non-family businesses due to the presence of stewards. However, strategic marketing decisions have unclear effects in achieving these outcomes. This study expands the literature on ST and SEW in FFs, integrating them with sustainable principles. We also contribute to the sustainability debate and marketing literature related to FFs.
Keywords: Corporate communication; CSR performance; Family firms; Socio-emotional wealth; Stewardship theory; Sustainability